United States. Continental Congress records - United States. Continental Congress
Original and reproduced records of the U.S. Continental Congress. Includes letters and extracts from letters, circular letters, extracts from journals and minutes of the congress and its committees, committee reports, orders, resolutions, contracts, oaths of allegiance to the United States, requisitions, financial documents, and lists. Subjects include finance, supplies, intelligence, personnel, political affairs, legislation, military matters, and Indian affairs.
Of note in the collection are a bundle of forty-six bills of exchange payable to Pierre Augustin Caron de Beaumarchais, supplier of arms and military stores to the United States, June 15, 1779; a group of fifteen letters (1777 January 17-1781 November 17) to the U.S. Continental Congress Secret Committee and Robert Morris from William Bingham, merchant and agent for Congress in St. Pierre, Martinique, and after his return to the United States; and an incomplete set of monthly attendance reports for delegates to the Congress, September 1785-May 1788.
Other persons represented include John Adams, John Dickinson, Horatio Gates, John Hancock, John Jay, John Paul Jones, Henry Laurens, Richard Henry Lee, James Madison, and Charles Thomson.
In part, facsimilies, transcripts, and photocopies.
Microfilm edition available, in part
Microfilm edition produced from originals in the Manuscript Division.
Microfilm edition only
Microfilm of originals in private hands.
Private.
Keywords: Adams, John, -- 1735-1826.; Beaumarchais, Pierre Augustin Caron de, -- 1732-1799.; Bingham, William, -- 1752-1804.; Dickinson, John, -- 1732-1808.; Gates, Horatio, -- 1728-1806.; Hancock, John, -- 1737-1793.; Jay, John, -- 1745-1829.; Jones, John Paul, -- 1747-1792.; Laurens, Henry, -- 1724-1792.; Lee, Richard Henry, -- 1732-1794.; Madison, James, -- 1751-1836.; Morris, Robert, -- 1734-1806.; Thomson, Charles, -- 1729-1824.; United States. -- Continental Congress. -- Secret Committee; Allegiance -- United States; Indians of North America -- Government relations; Finance, Public -- United States; Oaths -- United States; United States -- Appropriations and expenditures; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Equipment and supplies; United States -- History -- Revolution, 1775-1783 -- Secret service; United States -- History -- 19th century; United States -- Military policy; United States -- Politics and government -- 18th century